Respuesta :

Answer:

y = -5

Step-by-step explanation:

x= (-22+2y)/4 = -3+y

-22+2y = 4(-3+y)

-22+2y = -12+4y

-22+12 = 4y-2y

-10 = 2y

-10/2 = y

-5 = y

Answer:

x = -8

y = -5

Step-by-step explanation:

From the given expression, let's make two equations

4x   -   2y =   - 22--------------------------(i)

-x    +   y  =     3-----------------------------(ii)

to easily substitute, lets make another equation from equation (ii)

y  =  3  +   x

substitute (y=3+x) in equation (i)

4x   -   2 (x+3)   =   -22

4x  -   2x   -  6   =   -22

2x  -  6   =   -22

2x       =   -22   +  6

2x    =  -  16

x   = -16  /  2

x  =   -  8

lets solve for (y) by substituting   (x =  - 8) in equation   (ii)

-  (- 8)  +  y = 3

8  +  y  =   3

8  +  y  = 3

y  =  3  -  8

y  =  -  5

Therefore:

x  =  -  8

y  =  -  5

PLEASE FIND ATTACHED FILE

Maths is fun, keep learning!

Ver imagen lordsonmyk
ACCESS MORE